A Bicistronic Subgenomic mRNA Encodes both the ORF2 and ORF3 Proteins of Hepatitis E Virus - Graff, Judith (American Society for Microbiology, 2006)
Hepatitis E virus replicons containing the neomycin resistance gene expressed from open reading frames (ORFs) 2 and 3 were transfected into Huh-7 cells, and stable cell lines containing functional replicons were selected by constant exposure to G418 sulfate. Northern blot analyses detected full-length replicon RNA and a single subgenomic RNA. This subgenomic RNA, which was capped, initiated at nucleotide 5122 downstream of the first two methionine codons in ORF3 and was bicistronic; two closely spaced methionine codons in different reading frames were used for the initiation of ORF3 and ORF2 translation.